THE INFLUENCE RISK FACTORS OF STROKE ON DIABETES MELLITUS IN DR H. MOH ANWAR SUMENEP HOSPITAL - Sudarso Sudarso; Andre Setya Wahyudi (Fakultas Ilmu Kesehatan, 2014)
Diabetes mellitus (DM) is a group of metabolic diseases characterized with hiperglikemia happens because aberration secretion insulin, insulin work or both. Diabetes mellitus often caused many complications, one of which was stroke. With the cases number of diabetes, to be sure the number of stroke events will also be increased. Installation in the In a patient disease in dr H. Moh Anwar Sumenep Hospital. Diabetes mellitus was a disease with the highest visits increasing from year to year. Knowledge about the stroke incidence risk factors in people with diabetes mellitus is very important as a precaution against the occurrence stroke incident in people with diabetes mellitus. The objective of this research was to study the influence risk factors of stroke on diabetes mellitus. The research used method with a case control comparison of 1:1. Number of cases as many as 40 people (people with diabetes mellitus with stroke complications) and control as many as 40 people (people with diabetes mellitus without stroke complications). Data collected with the medical record and the laboratory examination results. Variables examined included age, sex, total cholesterol level, HDL level, LDL level, Trigliserida level, and hypertension history. Data analyzed using logistic regression test to see which factors affect the stroke incidence in people with diabetes mellitus. The result obtained that there were not influence of gender, HDL and LDL level and hypertension history to stroke occurrence in people with diabetes mellitus. The significant influence variables obtained age, total cholesterol level and Trigliserida level. the model if regression is = 1,103 - 0,564 (age) + 0,490 (total cholesterol level) + 0,258 (Trigliserida level). Based on the results of this study, patients needed counseling on diabetes mellitus on the efforts of the diabetes mellitus management that do not cause complications, one of which was stroke complication. Key words : diabetes mellitus, stroke, risk factors, dr. H Moh Anwar Sumenep Hospital